Microbiological analysis of commonly used toothpaste samples in Bangladesh - Talukder, Mousumi; Nur, Ifra Tun (Stamford Journal of Microbiology, 2019)
Present study attempted to identify and enumerate microorganisms spoiling commonly used toothpaste samples. Among 7 brand of toothpaste, almost all were found to be rigorously contaminated with total viable bacteria within a range of 103 – 105 cfu/g. Proliferation of fungal species was observed up to 105 cfu/g. Prevalence of Staphylococcus spp., Pseudomonas spp. and Bacillus spp. was observed within a range of 103-105 cfu/g while Vibrio spp. were completely absent. Among the enteric bacteria, Escherichia coli and Klebsiella spp. was found in all the samples tested. Such findings highlighted a great public health risk associated with dental diseases among the users and thereby specified the importance to introduce a proper guideline in maintaining good microbiological quality for such daily usage healthcare products. Stamford Journal of Microbiology, Vol.8(1) 2018: 38-40